Choice of treatment and diagnostic tactics at nonpalpable breast tumors - Ye. P. Kulikov; M. Ye. Ryazantcev; A. P. Zagadaev; Ye. L. Sashina; I. Yu. Vinogradov (Опухоли женской репродуктивной системы, 2014)
Results of inspection, treatment and dynamic supervision of 166 patients with nonpalpable breast tumors are presented. Distribution of tumors on BI-RADS system is given. Possibilities of a mammography and ultrasonography in diagnostics of a preclinical breast cancer are shown. Practical recommendations about a choice of an optimum way of presurgical verification of nonpalpable tumors are offered. Indications for surgical treat- ment and dynamic supervision are specified at nonpalpable breast tumors.